Unraveling University Students’ Socio-Psychological Needs in Chinese Cultural Context: Grounded in Maslow’s Hierarchy of Needs - Xuanwei Cui (Eastasouth Institute, 2023)
Abraham Maslow, a pioneer and founder of humanistic psychology, put forward Maslow’s Hierarchy of Needs which comprises five stages: Physiological Needs, Needs for Safety, Needs for Love and Social belongings, Needs for Respect, and Needs for Self-Actualization. Hierarchy is one of the noteworthy features of Maslow’s Hierarchy of Needs. Given the cultural context of Chinese universities where students are inherently influenced by Confucianism and collectivist national culture, attending to their needs at each of the five stages is instrumental for their success in life. To better tackle the psychological issues that students from universities may have, leaders at universities need to establish organizational policies and provide efficient counseling services to students from universities in China.